Radiocarbon Dating of Mortars with a Pozzolana Aggregate Using the Cryo2SoniC Protocol to Isolate the Binder. Issue 2 (5th December 2017) - Nonni, Sara; Marzaioli, Fabio; Mignardi, Silvano; Passariello, Isabella; Capano, Manuela; Terrasi, Filippo
Abstract: To date, finding a technique able to effectively isolate the carbon signal from the binder of a mortar is still an open challenge. In this paper, the radiocarbon ( 14 C) dating of one of the most challenging and diffuse types of mortar, the one with pozzolana aggregate, is investigated. Eight mortar samples from three archaeological sites near Rome (Italy) underwent a selection process called Cryo2SoniC. The selected fractions were analyzed by the accelerator mass spectrometry (AMS) 14 C technique and compared to known historical references. Additional scanning electron microscopy analysis and petrographic investigations were done, respectively, to check the grain size of the fractions selected by Cryo2SoniC, and further, to characterize the original mortar samples. The masses of carbon yielded from the dated fractions were almost half of those released from some aerial mortars. The 14 C dating results were accurate for pozzolana mortars, from buried and unburied structures, with calcination relics and small contamination of secondary calcite. A limitation in the purification protocol was observed on samples with a massive contamination of secondary calcite deposition of ground water origin, occluding porosity and substituting up to the 80% of the original binder matrix.